Comparing Dried Blood Spots and Plasma Concentrations for Busulfan Therapeutic Drug Monitoring in Children. Issue 1 (February 2020) - Dilo, Ana; Daali, Youssef; Desmeules, Jules; Chalandon, Yves; Uppugunduri, Chakradhara R. S.; Ansari, Marc
Abstract : Background: Busulfan (Bu) is one of the conditioning regimen components for pediatric hematopoietic stem cell transplantation. Bu therapeutic drug monitoring (TDM) is essential for a successful treatment outcome and toxicity evasion. Dried blood spot (DBS) sampling is a rapid and simple method for Bu TDM, compared with conventional plasma sampling. This study evaluated the feasibility of using the DBS method for Bu TDM. The hematocrit (Hct) and conditioning day were also examined for their impact on the DBS method's performance. Methods: Venous blood collected from 6 healthy volunteers was diluted, using their plasma into 4 samples of varying Hct values. Each sample was spiked with Bu calibrators (300, 600, and 1400 ng/mL), prepared using DBS and dried plasma spot (DPS) sampling and analyzed using a validated liquid-chromatography tandem-mass spectrometry method. Clinical blood samples (n = 153) from pediatric patients (n = 15) treated with Bu (mainly from doses 1, 2, 5, and 9) were used to prepare paired volumetric DBS and DPS samples. A Bland–Altman plot and Deming regression were used to define the agreement between the paired DBS and DPS measurements. Passing–Bablok regression analyses investigated the effects of Hct and conditioning day on the linearity between both methods. Results: In vitro analyses showed good agreement between DBS and DPS measurements, with a mean difference of −5.4% and a 95% confidence interval on the limits of agreement of −15.3% to 4.6%. Clinical samples showed good correlation (Pearson correlation coefficient = 0.96; slope = 1.00) between the DBS and DPS methods. The DBS method met the clinical acceptance limits for clinical samples, with a bias <±20%. Bland–Altman plots showed good agreement, with only 5.8% of paired measurements exceeding the limits of agreement (±1.96 SD), although within its 95% confidence interval. Hct observations ranged from 21.7% to 34.7% and did not affect Bu concentrations measured from DBS in either the in vitro or in vivo studies. Conclusions: These results show that DBS is a useful method for Bu TDM, provided samples are analyzed on the collection day. DBS sampling offers advantages over traditional plasma sampling in infants and younger children because only small volumes of blood are required. Abstract : Supplemental Digital Content is Available in the Text.